IMPACT OF TECHNOLOGY TRANSFORMATION ON SERVICE QUALITY: SERVICE SPEED AS A MEDIATING VARIABLE IN VEHICLE INSPECTION SECTOR - Suwandi, Hikmatur Rizka (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study explores the impact of technological transformation on service quality in vehicle KIR testing services at the Jember Regional Office of the Transportation Agency, emphasizing the mediating role of service speed. Method: Using a quantitative research approach with Structural Equation Modeling (SEM) via SmartPLS 4, the study analyzes data collected from 190 respondents who utilized KIR services. Results: The findings demonstrate that technological transformation significantly enhances service speed and service quality, with service speed serving as a critical intermediary in translating technological advancements into improved user satisfaction. The adjusted R² values indicate that 41.2% of the variance in service speed and 74.8% of the variance in service quality are explained by technological transformation and service speed. Novelty: These results highlight the importance of integrating digital infrastructure with operational efficiency to optimize public service delivery. The study provides theoretical contributions to the understanding of service speed as a mediating factor while offering practical recommendations for policymakers to prioritize digital transformation initiatives in enhancing public service quality. Limitations of the study and avenues for future research are also discussed to expand the generalizability of the findings.